PERKEMBANGAN HIDUP DAN DAYA MEMANGSA CURINUS COERULEUS MULSANT PADA BEBERAPA KUTU TANAMAN - Nur Yasin . (Universitas Lampung, 2006)
The biological development and feeding ability of Curinus coeruleus Mulsant on several phytophthires. The research was conducted to investigate the survival and feeding capability of Curinus coeruleus Mulsant on Heteropsylla cubana, Aleurocanthus spiniferus, Planococcus citri, and Aspidiotus destructor. The research was done in completely randomized design with eight replications. The result showed that C. coeruleus could not survive on A. spiniferus. The head width of C. coeruleus larvae did not differ significantly in A. destructor, P. citri, or H. cubana. The head width increase of C. coeruleus larvae feeding on A. destructor followed Dyar’s law with growth ratio of 1,4. Larval stadium of C. coeruleus, imago stadium, longevity, and the number of consumed preys were affected by phytophthires species. C. coeruleus could feed on more H. cubana than A. destructor, or P. citri.